Hearing modulation affects Alzheimer’s disease progression linked to brain inflammation: a study in mouse models - Yoo-Seung Ko; Young-Kyoung Ryu; Sujin Han; Hyung Joon Park; Munyoung Choi; Byeong C. Kim; Han-Seong Jeong; Sujeong Jang; Jihoon Jo; Sungsu Lee; Won-Seok Choi; Hyong-Ho Cho (Molecular Medicine, 2024)
Abstract Background Recent studies have identified hearing loss (HL) as a primary risk factor for Alzheimer’s disease (AD) onset. However, the mechanisms linking HL to AD are not fully understood. This study explored the effects of drug-induced hearing loss (DIHL) on the expression of proteins associated with AD progression in mouse models. Methods DIHL was induced in 5xFAD and Tg2576 mice aged 3 to 3.5 weeks using kanamycin (700 mg/kg, subcutaneous) and furosemide (600 mg/kg, intraperitoneal). The accumulation and expression of beta-amyloid (Aβ), ionized calcium-binding adaptor molecule 1 (Iba1), and glial fibrillary acidic protein (GFAP) were measured through immunohistochemistry and immunoblotting. Additionally, the expression of proteins involved in the mammalian target of rapamycin (mTOR) pathway, including downstream effectors p70 ribosomal S6 kinase (p70S6K) and S6, as well as proinflammatory cytokines, was analyzed. Results Compared to control conditions, HL led to a significant increase in the accumulation of Aβ in the hippocampus and cortex. Elevated levels of neuroinflammatory markers, including Iba1 and GFAP, as well as proinflammatory cytokines such as interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-alpha (TNF-α), were observed. Moreover, DIHL enhanced phosphorylation of mTOR, p70S6K, and S6, indicating activation of the mTOR pathway. Conclusions HL significantly increases Aβ accumulation in the brain. Furthermore, HL activates astrocytes and microglia, leading to increased neuroinflammation and thereby accelerating AD progression. These findings strongly suggest that HL contributes autonomously to neuroinflammation, highlighting the potential for early intervention in HL to reduce AD risk.